2011
DOI: 10.4085/1062-6050-46.4.409
|View full text |Cite
|
Sign up to set email alerts
|

Between-Seasons Test-Retest Reliability of Clinically Measured Reaction Time in National Collegiate Athletic Association Division I Athletes

Abstract: Context: Reaction time is typically impaired after concussion. A clinical test of reaction time (RT clin ) that does not require a computer to administer may be a valuable tool to assist in concussion diagnosis and management.Objective: To determine the test-retest reliability of RT clin measured over successive seasons in competitive collegiate athletes and to compare these results with a computerized measure of reaction time (RT comp ).Design: Case series with repeated measures. Setting: Preparticipation phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 24 publications
4
55
1
1
Order By: Relevance
“…Future concussion consensus group research recommendations have suggested the looking at efficacy for inclusion of vision tests such as King-Devick and clinical reaction time tests, which will have limitations for many athletes with disability including those with visual impairment 8,40,41 or neuromuscular impairment, such as cerebral palsy. Furthermore, learning disability often goes unrecognized in sporting environments.…”
Section: Au10mentioning
confidence: 99%
“…Future concussion consensus group research recommendations have suggested the looking at efficacy for inclusion of vision tests such as King-Devick and clinical reaction time tests, which will have limitations for many athletes with disability including those with visual impairment 8,40,41 or neuromuscular impairment, such as cerebral palsy. Furthermore, learning disability often goes unrecognized in sporting environments.…”
Section: Au10mentioning
confidence: 99%
“…The ruler drop test was used to assess average reaction speed, a simple and inexpensive test compared to computerized assessments, with comparable reliability [27][28][29][30]. Participants carried out three practice runs to eliminate a learning effect [27].…”
Section: Reaction Timementioning
confidence: 99%
“…Al though estimates of reliability of the intraclass correlation coefficient ICC > 0.90 was ideal, this seems to be an unrealistic point of reference for a test evaluation of something as complex as the processing speed of the brain for prolonged periods of time 20 as proposed in the assessment of mental fatigue test from TRT.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of testing with RT stimulate some authors to propose in struments more affordable for clinical application, validating with other software 20 or a RT Electronic Tester 21 . In young adults the performances in TRT with simple visual stimuli were highly correlated, where as with the evaluation test of mental fatigue correlation was intermediate to the initial stimulus and very little with the final stimulus.…”
Section: Discussionmentioning
confidence: 99%